Surveillance Imaging following Endovascular Aneurysm Repair: State of the Art - Kim, Stephanie H.; Litt, Harold I. (Seminars in Interventional Radiology, 2020)
Endovascular aneurysmal repair (EVAR) has become a prominent modality for the treatment of abdominal aortic aneurysm. Surveillance imaging is important for the detection of device-related complications, which include endoleak, structural abnormalities, and infection. Currently used modalities include ultrasound, X-ray, computed tomography, magnetic resonance imaging, and angiography. Understanding the advantages and drawbacks of each modality, as well available guidelines, can guide selection of the appropriate technique for individual patients. We review complications following EVAR and advances in surveillance imaging modalities.
Keywords: abdominal aortic aneurysm; endovascular aneurysm repair; surveillance imaging; endoleak; interventional radiology